ANALISIS KINERJA KONSULTAN MANAJEMEN KONSTRUKSI TAHAP IMPLEMENTASI PADA PROYEK KONSTRUKSI - Eka Priana, Surya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Reflected by the many stages in a project life cycle or Project Life Cycle. Of all these stages, the implementation (construction) stage is the stage that needs serious attention, because this stage must be achieved on time, at the right cost and at the right quality or what is often referred to as the triple constraint. For this reason, a good project management system is needed, such as that offered by Construction Management Consultants (KMK). This research aims to identify and create an instrument for measuring KMK performance at the implementation stage. There are 5 (five) performance indicators which have been developed into 22 (twenty two) variables used to measure KMK performance on government and private projects. Next, analysis was carried out using the Customer Satisfaction Index (CSI) method. From the results of the analysis and calculation of the measured KMK performance, the CSI value for KMK performance on government projects was 52.51% (quite satisfied) and the CSI for KMK performance on private projects was 85.88% (very satisfied).Keywords: Construction Management Consultant System, indicators, variables, customer satisfaction index.